2016
DOI: 10.17576/mjas-2016-2003-15
|View full text |Cite
|
Sign up to set email alerts
|

QUANTIFICATION OF CATECHIN IN LEAVES AND STEMS OF MALAYSIAN Uncaria gambir (HUNTER) ROXB. BY HPLC-DAD

Abstract: Recently, we reported the isolation of a novel flavonoid named uncariechin along with epicatechin and epiafzelechin from the leaf extract of Uncaria longiflora variety pteropoda (Miq.) Ridsd. of the family Rubiaceae. Continuing our investigation on the Uncaria genus, the identification and quantification of its phytoconstituents was carried out. The species of particular interest is the Malaysian Uncaria gambir. This species is distributed mainly in Malaysia and Indonesia and has been cultivated for the flavon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Phytochemical content detected in gambir leaves were mostly catechin (50%), pyrocatechol (20-30%), gambirin (1-3%), red kateku 3-5 (3-5%), quercetin (2-4%), wax (1-2%), and alkaloids (2-5%) (Nurdin and Fitrimiwati, 2018). Ibrahim et al (2016) also reported that the main content of gambir was catechin. Catechin content of gambir was about 50.87-55.40% (Anggraini et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
“…Phytochemical content detected in gambir leaves were mostly catechin (50%), pyrocatechol (20-30%), gambirin (1-3%), red kateku 3-5 (3-5%), quercetin (2-4%), wax (1-2%), and alkaloids (2-5%) (Nurdin and Fitrimiwati, 2018). Ibrahim et al (2016) also reported that the main content of gambir was catechin. Catechin content of gambir was about 50.87-55.40% (Anggraini et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
“…The crude extract was dissolved in 1% DMSO at a concentration of 2000 ”g/mL using the test tube shaker. Later, the mixture was ltered through a 0.2 ”m syringe lter to obtain a puri ed Uncaria gambir extract [14]. Subsequently, the puri ed extract underwent a 2-fold serial dilution into 8 different concentrations ranging from 1000 ”g/mL of the extract in 0.5% DMSO to 7.8 ug/mL of extract in 0.0039% DMSO.…”
Section: Preparation Of Test Materialsmentioning
confidence: 99%
“…12 Catechin has been reported as the main bioactive compounds and has been used as metabolite biomarker to determine the quality of gambir. 13 A comprehensive study by Nonaka found a new bioflavonoid compound, gambiriin. Gambir also contains the yellow flavonoid quercetin, as well as gambirdin and isogambirdin.…”
Section: A Phytochemical Compoundmentioning
confidence: 99%